Halal Horizons: Revolutionizing Supply Chains At Indonesian’s Fishery Port - Himawan, Abdurrahman Faris Indriya; Sidik, Mohamad Hazeem; Hasan, , Md Zaki Muhamad; Suryana, Irma Sonya; Aziz, Wan Muhammad Azim bin Wan Abdul (Devotion : Journal of Research and Community Service, 2023)
The purpose of this study is to examine the supply chain management process carried out by fishermen in their search for fish at a Fishery Port in East Java, Indonesia. In this study, the researcher directly observed the supply chain management process at the port. Additionally, the researcher analyzed how this process aligns with Islamic Sharia, ensuring that the supply chain activities are considered halal (permissible) and toyyib (wholesomeness). This study employed a qualitative case study method using the Miles and Huberman analysis technique (data reduction, data display, and data verification). The processes involved all stages from the sea and to the end of the supply chain where the catch was being sold to customers. Based on the objective of examining halal supply chain management, the researcher found that the activities performed by the fishermen at the port can be considered halal and toyyib. As this study is only focusing on upstream, future researchers could focus on the full-scale supply chain.